Mid-IR narrow bandwidth tuneable laser source for the FAMU experiment - Baruzzo Marco; Suárez-Vargas José J.; Stoychev Lyubomir I.; Cabrera Humberto; Toci Guido; Moretti Luigi; Fasci Eugenio; Gianfrani Livio; Pizzolotto Cecilia; Mocchiutti Emiliano; Danailov Miltcho B.; Vacchi Andrea (EPJ Web of Conferences)
The FAMU (Fisica degli Atomi MUonici) collaboration aims to measure the proton Zemach radius through muonic hydrogen (μp) spectroscopy. The experimental setup relies on a custom-developed pulsed mid-IR laser source that can be tuned over a specific 6780-6790 nm wavelength range needed to ignite the hyperfine transition of the μp ground state 1S (also known as spin-flip transition). The excitation is observed as a distinctive muonic X-rays emission resulting from the oxygen impurity present in the hydrogen target. The mid-IR emission is produced by Difference Frequency Generation (DFG) in a non-linear crystal, pumped with a fixed wavelength 1064 nm Nd-YAG laser and a tuneable Cr:forsterite laser centred on 1262 nm. This setup produces more than 1.2 mJ at 6780 nm with a linewidth smaller than 30 pm. The experiment requires the laser to run continuously 24/7 in a restricted/radiation-controlled area and for this reason a specifically developed control software permits to remotely act on the laser. The characterization of a series of different non-linear crystals was performed during the development of the laser, resulting in the choice of BaGa4Se7.